Textual Games - Wachowski, Jacek (Przestrzenie Teorii, 2024)
The article attempts to characterize literary practices which have emerged in recent decades due to the rise of new technologies. The titular “textual games” are experiments which test the stylistic and genre durability of popular literary works. They give rise to new technological formats and new genre variations (gamebooks or works written by artificial intelligence). As such, they also create a new and unique aesthetic and formal landscape and provoke reflection on contemporary literary practices and research strategies that can be used to describe them.